2005
DOI: 10.1074/jbc.m412548200
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Regulatory Regions of Emilin1 Gene and Their Combinatorial Contribution to Tissue-specific Transcription

Abstract: The location of regions that regulate transcription of the murine Emilin1 gene was investigated in a DNA fragment of 16.8 kb, including the entire gene and about 8.7 and 0.6 kb of 5-and 3-flanking sequences, respectively. The 8.7-kb segment contains the 5-end of the putative 2310015E02Rik gene and the sequence that separates it from Emilin1, whereas the 0.6-kb fragment covers the region between Emilin1 and Ketohexokinase genes. Sequence comparison between species identified several conserved regions in the 5-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The expression of the transgenic Emilin1 promoter in embryos reproduced the complexity expected from the distribution of endogenous gene products ( Figure I in the online-only Data Supplement). 1,3,9 Matching of this promoter activity with that of the endogenous gene was investigated in mice harboring the human EMILIN1 cDNA in Emilin1 +/− embryos. As shown in Figure Table).…”
Section: Transgenes Expression Patternsmentioning
confidence: 99%
“…The expression of the transgenic Emilin1 promoter in embryos reproduced the complexity expected from the distribution of endogenous gene products ( Figure I in the online-only Data Supplement). 1,3,9 Matching of this promoter activity with that of the endogenous gene was investigated in mice harboring the human EMILIN1 cDNA in Emilin1 +/− embryos. As shown in Figure Table).…”
Section: Transgenes Expression Patternsmentioning
confidence: 99%
“…The gC1q domain of Emilin1 can form relatively stable and compact homotrimers, and then be followed by a multimeric assembly of disulfide-bonded protomers. The transcription of Emilin1 in different tissues is probably achieved through combinatorial cooperation between various regions, rather than being dependent on a single cis-activating region specific for each tissue [27]. Emilin1 code for a secreted proteins whose hallmark is the presence of a cysteine-rich motif defined as EMI domain [28] that followed by a coiled-coil, a short collagenous domain, and a C1q-like repeat at the C terminus which has been shown that the C-terminal domain is involved in the oligomerization of Emilin1, cell adhesion and modulating growth factors' activity [29].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, EMI domain has been found related to mesenchymal commitment during an early stage of skeletal development, indicating that EMILIN-5 might also contribute to skeletal development. (2,3) EMILIN-5 was found expressed in human mesenchymal stem cells. (1) Thus far, however, the functions of EMILIN-5 remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%